"Vikingland" and the Epic of Emigration - Cascudo, José Antonio (Madrygal. Revista de Estudios Gallegos, 2015)
This article focuses on the construction of cultural identity through Galician audiovisual production, taking the film Vikingland (2011) by Xurxo Chirro as a reference. The purpose of this study is to explore the leitmotifs of the migratory phenomenon by comparing this production with other related works such as Mamasunción or Avión, el pueblo ausente in order to build a visual repository of Galician collective memory.